Impact of diabetes mellitus on endodontic treatment outcomes - Alshargawi, Waleed K.; Alghamdi, Faris M.; Alziyad, Saeed A.; Ramadan, Feras L.; Alamoudi, Asma I.; Alotni, Soltan; Saad, Raghad M.; Alsayegh, Ali S.; Altwalah, Abdullah A.; Alharbi, Ruba F.; Alshehri, Maram M. (International Journal Of Community Medicine And Public Health, 2024)
Diabetes mellitus (DM) is a chronic metabolic disorder that affects various systemic functions, including oral health. Its impact on endodontic treatment outcomes has become a significant concern for dental practitioners. The relationship between DM and endodontic outcomes is complex, involving several pathophysiological mechanisms. Hyperglycemia leads to the formation of advanced glycation end-products, causing vascular dysfunction and impaired blood supply to the pulp, which exacerbates pulpal inflammation and increases the risk of necrosis. Additionally, chronic low-grade inflammation and an impaired immune response in diabetic patients contribute to a higher susceptibility to infections, delayed healing, and compromised tissue repair after endodontic procedures. Diabetic patients often experience lower success rates and prolonged recovery following endodontic treatment due to these systemic challenges. Reduced bone healing, persistent periapical lesions, and altered microbial flora are common complications that can hinder treatment success. Effective management of endodontic treatment in diabetic patients requires a multifaceted approach that includes strict glycemic control, the use of enhanced antimicrobial strategies, and the adoption of minimally invasive techniques to reduce tissue trauma. Additionally, patient education and close monitoring of the healing process are essential for minimizing complications. Understanding the pathophysiological interactions between diabetes and pulpal inflammation, as well as the factors that influence healing and success rates, is crucial for optimizing endodontic care in diabetic patients. By addressing both systemic and local factors, dental practitioners can improve the prognosis of endodontic treatment and ensure better outcomes for patients with diabetes. Ongoing research into the mechanisms underlying these complications will further enhance the ability of clinicians to manage endodontic cases effectively in this growing patient population.